Participation of private sector companies in emerging capital markets: A study of capital markets in Tanzania - Nangawe, Abbi Godfrey (Mzumbe University, 2023)
A Dissertation Submitted in Partial Fulfillment of the Requirements for Award of Degree of Doctor of Philosophy of Mzumbe University.